EXPLORING SELJE TOPOLOGICAL SPACE: APPLICATION IN OPTIMIZING RENAL HEALTH - V, Jeyanthi.; Selva, Nandhini N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Renal health is vital for maintaining overall body homeostasis, and dysfunction in the kid- neys can lead to severe complications, including chronic kidney disease and cardiovascular problems. Identifying the factors that contribute most significantly to renal impairment is criti- cal for early diagnosis and effective treatment. This study utilizes the Selje Topological Space framework to analyze renal health factors. Data was collected over several months from pa- tients with renal dysfunction, focusing on key contributors such as hemoglobin, blood urea nitrogen, azotocreatinine, estimated glomerular filtration rate (eGFR), and potassium levels. The Selje Topological Space approach was used to identify the primary determinants of kidney dysfunction. The analysis revealed that urea and potassium levels were the most significant factors affecting kidney function under normal sugar conditions. In cases where blood sugar levels were abnormal, urea was identified as the dominant contributor to renal impairment. The study’s findings emphasize the importance of monitoring urea and potassium levels in patients at risk for renal disease. These insights can guide clinical interventions and improve strategies for preventing kidney dysfunction in patients with both normal and abnormal blood sugar lev- els.